CONSUMER BEHAVIOR DURING THE COVID-19 OUTBREAK: AN ANALYSIS FOR DECISION MAKING, PREFERENCES AND FUTURE CONDITIONS - Haile Qudrat Djojodibroto; Istiningsih Istiningsih; Rum Mohamad Andri K.R (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The COVID-19 outbreak has caused a catastrophic global terror. Several industries have been impacted. Customers' dissatisfaction is a challenge to coffee business entrepreneurs. It has an effect on coffee consumer behavior, particularly purchases made at coffee shops. The purpose of this study is to evaluate consumer motivation to buy coffee and the decision-making process of consumers buying coffee during a pandemic. This article provides an in-depth examination of the elements that influence customer behavior and purchasing decisions in marketing. Discerning patterns to rectify these requirements, making purchasing decisions such as whether to purchase goods and services and, if so, which types of brands and where, interpreting advice, establishing plans, and carrying out these plans, such as comparative shopping or actual product purchases, Totally, contemporary and professional marketing staff strive to understand customers and their answers, and so they analyze the key characteristics of their behavior.